Harsh Times: Do Stressors Lead to Labor Market Losses? - Terhi Maczulskij; Petri Böckerman (Institute of Labor Economics (IZA), 2017)
This paper examines the effects of past stressful life events on subsequent labor market success using data on twins matched to comprehensive register-based, individual-level information on income and employment status. The long-term labor market outcomes are measured during 20-year follow-up. We use the within-twin method to account for unobservable family and genetic confounders. The twin design reveals three important findings. First, stressors lead to worse labor market outcomes. Second, men are more affected by financial and job-related stressors, while women are more affected by family stressors. Third, the negative effects that stressors have on labor market outcomes diminish as time passes.
Keywords: I31; J24; J31; 330; stressors; stressful life events; employment; earnings; co-twin control; twins